2021
DOI: 10.3389/fbioe.2020.579788
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide Releasing Hydrogel Nanoparticles Decreases Epithelial Cell Injuries Associated With Airway Reopening

Abstract: Acute respiratory distress syndrome (ARDS) is an acute inflammatory lung condition. It is characterized by disruption of gas exchange inside the alveoli, accumulation of protein edema, and an increase in lung stiffness. One major cause of ARDS is a lung infection, such as SARS-COV-2 infection. Lungs of ARDS patients need to be mechanically ventilated for airway reopening. Consequently, ventilation might damage delicate lung tissue leading to excess edema, known as ventilator-induced lung injury (VILI). Mortali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…ARDS is characterized by diffuse alveolar damage and compromised gas exchange, lung stiffness, and edema [ 34 , 65 ], with patients experiencing shortness of breath and hypoxemia, many requiring mechanical ventilation (MV) [ 66 ]. Mortality rates among COVID-19 patients requiring invasive mechanical ventilation (IMV) are reportedly high, with an estimated overall fatality rate of 45% among 57,420 COVID-19 IMV cases from 69 studies [ 67 ].…”
Section: Major Features Of Covid-19 Infection: Points Of Interventionmentioning
confidence: 99%
See 1 more Smart Citation
“…ARDS is characterized by diffuse alveolar damage and compromised gas exchange, lung stiffness, and edema [ 34 , 65 ], with patients experiencing shortness of breath and hypoxemia, many requiring mechanical ventilation (MV) [ 66 ]. Mortality rates among COVID-19 patients requiring invasive mechanical ventilation (IMV) are reportedly high, with an estimated overall fatality rate of 45% among 57,420 COVID-19 IMV cases from 69 studies [ 67 ].…”
Section: Major Features Of Covid-19 Infection: Points Of Interventionmentioning
confidence: 99%
“…The anti-inflammatory properties of NO are also promising for reducing ventilator-induced lung injury (VILI). In a model of shear-stress induced epithelial cells resembling VILI, pre-treatment with NO-releasing nanoparticles pre-and post-exposure reduced cell injury and cell death, with ROS and IL-6 levels significantly reduced [ 65 ]. These findings indicate a potential in severe COVID-19 cases to curtail excessive inflammation and ameliorate lung injury through MV.…”
Section: No For Management Of Hyperinflammationmentioning
confidence: 99%
“…Finally, the levels of reactive ROS in each group were assessed. AFM studies showed that NO exposure alters cell shape before and after shear exposure, and qRT-PCR revealed a significant decrease in IL6 and CCL2 production when the cells were treated with NO through nanoparticles [46]. Statistical shape modeling was used to create four diseased lung models with different degrees of bronchial dilation and constriction in the left-lower lobe.…”
Section: Regeneration Of Lung Tissues Using Biopolymeric Nanoparticles For Covid-19 Patientsmentioning
confidence: 99%
“…The main areas of research include studying the transmission of COVID-19 and facilitating its detection, developing possible vaccines and treatments, and understanding the social and economic impacts of the pandemic. [1][2][3][4][5] Also researchers worldwide have been working to provide clothing and protective tools for doctors as well as the nursing staff to provide protection from disease transmission as well as providing comfort and flexibility for ease of work. [4][5][6] In addition to provide tools for patients for ease of household insulation, such as devices for measuring temperature, respiration and pressure.…”
Section: Introductionmentioning
confidence: 99%